Prenatal and postnatal diagnosis of Phelan–McDermid syndrome: A report of 21 cases from a medical center and review of the literature - Hao, Ying; Liu, Yang; Yang, Jingxin; Li, Xingping; Luo, Fuwei; Geng, Qian; Li, Suli; Li, Peining; Wu, Weiqing; Xie, Jiansheng (Frontiers in Genetics, 2022)
Background: Phelan–McDermid syndrome (PMS) caused by deletions at 22q13.3 and pathogenic variants in the SHANK3 gene is a rare developmental disorder characterized by hypotonia, developmental delay (DD), intellectual disability (ID), autism spectrum disorder (ASD) and dysmorphic features. Methods: Conventional karyotyping, chromosome microarray analysis (CMA), and whole exome sequencing (WES) have been used to detect genetic defects causing PMS. We summarized the genetic and clinical findings from prenatal to postnatal stages of detected cases of PMS and mapped potential candidate haploinsufficient genes for deletions of 22q13. Results: Seven prenatal cases and 14 postnatal cases were diagnosed with PMS in our center. Thirteen cases had a deletion ranging in size from 69 Kb to 9.06 Mb at 22q13.2-q13.33 and five cases had a pathogenic variant or an intragenic deletion in the SHANK3 gene. Three familial cases with a parental carrier of a balanced translocation were noted. Review of literature noted another case series of 29 cases and a report of five cases of PMS in China. Genotype-phenotype correlations confirmed haploinsufficiency of the SHANK3 gene for PMS and suggested other candidate haploinsufficient genes TNFRSFI3C and NFAM1 genes for immunological features, and TCF20, SULT4A1, PARVB, SCO2 and UPK3A genes for neurological features, macrocephaly/hypotonia, oculopathy and renal adysplasia, respectively. Conclusion: The indications for prenatal diagnosis of PMS are not specific and approximately 85% prenatally diagnosed PMS elected termination of pregnancies after genetic counseling. For postnatal cases, 62.5% were caused by a deletion at 22q13 and 37.5% were caused by a pathogenic variant or an intragenic deletion in the SHANK3 gene; approximately 6.7% of cases with a deletion were familial and almost all pathogenic variants were de novo. Combined karyotype, CMA and WES should be performed to increase the diagnostic yield. The identification of other candidate haploinsufficient genes in deletions of 22q13.2-q13.33 could relate to more severe dysmorphic features, neurologic defects, and immune deficiency. These results provided evidence for diagnostic interpretation, genetic counseling, and clinical management for Chinese cases of PMS.